Impossible Paradise: Sex and Functional Diversity in Oasis (Oasiseu, 2002) (Anclajes, 2019)
Sexual desire in women with functional diversity has hardly been portrayed in films in such an explicit way as in Oasis (Oasiseu, 2012), a raw and romantic drama in equal measure directed by the South Korean auteur Lee Chang-Dong. Through the female protagonist, a young woman with severe cerebral palsy who is confined in her apartment and subject to family and social exclusion, Lee Chang-dong offers a real-life moving portrait of functional diversity. The film denounces prejudices and social stereotypes and dismantles normative femininity, which assumes that a functionally diverse woman possesses an asexual body.
Keywords: Lee Chang-dong; Oasis; functional diversity; sexuality; film analysis